5G mobile/multi-access edge computing integrated architecture and deployment strategy - Jianmin ZHANG; Weiliang XIE; Fengyi YANG; Zhouyun WU (Dianxin kexue)
Mobile/multi-access edge computing (MEC) technology migrates computing storage capabilities and service service capabilities to the edge of the network,enabling applications,services and content to be localized,close-range and distributed.Therefore,to a certain extent,the business requirements of 5G enhanced mobile broadband,low latency and high reliability and large-scale machine communication terminal connection are solved.At the same time,the MEC fully exploits mobile network data and information to implement the awareness and analysis of context information of the mobile network and open it to third-party service applications.This effectively enhances the level of intelligence in mobile networks and promotes the deep integration of networks and services.Therefore,the value and significance of the MEC was firstly analyzed according to the typical 5G service scenario.Secondly,based on the research progress of ETSI and 3GPP,a MEC fusion architecture oriented to 5G was proposed,and the overall deployment strategy of MEC was discussed and analyzed.Furthermore,the possible problems and challenges in the future application of MEC technology in 5G networks were discussed to provide reference for subsequent research and development.